Post-traumatic neuroma of the mental foramen area - case report - Agnieszka Kaja; Jolanta Białkowska-Głowacka; Monika Ratajek-Gruda; Anna Janas-Naze (Kazimierz Wielki University, 2019)
The article presents a case of a patient in which an asymptomatic intraosseous tumor of the mental nerve area was removed. The result of histopathologic examination confirmed the initial diagnosis of post-traumatic neuroma.